Intra-operative digital specimen radiology reduces re-operation rates in therapeutic mammaplasty for breast cancer. Issue 5 (October 2015) - Majdak-Paredes, E.J.; Schaverien, M.V.; Szychta, P.; Raine, C.; Dixon, J.M.
Abstract Background The aim of this study was to evaluate our experience with intra-operative imaging of therapeutic mammaplasty specimens at Edinburgh Breast Unit. Methods A retrospective review was performed of patients who underwent therapeutic mammaplasty in Edinburgh Breast Unit between 2007 and 2013 who had intraoperative specimen radiography. Results 98 (100%) patients who underwent therapeutic mammaplasty for breast cancer had intra-operative imaging using the faxitron® system. 3 out of those 97 (3%) patients had a re-operation because of positive margins confirmed pathologically on cavity excision specimens, but only 1 out of 3 (1%) patients had residual breast cancer present within the re-excision specimen. None required mastectomy. Median age was 58 (range 34–81). Median follow up was 3.1 years (range 6 months – 5.5 years). There was no local recurrence or conversion to mastectomy in this group. Conclusion Complete excision rate in patients who had intra-operative imaging during therapeutic mammaplsty procedure was 97% in our group. Faxitron® system is a useful adjunct in helping to achieve low incomplete excision rates.